Uji Daya Hasil Padi Hibrida 1683, 1606 dan 358 pada Jarak Tanam yang Berbeda - Samanhudi Samanhudi; Bambang Pujiasmanto; Ahmad Yunus; Hadiandra Harfiansyah (Agrosains : Jurnal Penelitian Agronomi, 2015)
Rice is the main commodity food support in Indonesian society. As a country with a large population, there are challenges to improve the efficiency and optimizing the utilization of land resources. The purpose of this study is to determine the use of lines were superior and spacing are effective in increasing productivity. The research was conducted at the experimental land Faculty of Agriculture, Sebelas Maret University, Mojolaban, Sukoharjo. The research using Randomized Completely Block Design. The first factor is the lines, local lines Inpari 10, hybrid rice lines Tiongkok 1683, 1606, and 358. The second factor is the plant spacing, 18 cm x 18 cm, 22 cm x 22 cm, and 26 cm x 26 cm. Data were analyzed using analysis of variance and if there is a significant followed by Duncan Multiple Range Test at 5% level. Hybrid rice lines 358 and spacing of 26 cm x 26 cm is a combination of treatments that have a higher level of productivity is 5.86 ton/ha.